Analysis Of The Impact Of The Shopee Application On Students' Wasteous Behavior - Eka Risma Wati; Syarif As’ad As’ad (Al-Hijrah: Journal of Islamic Economics And Banking, 2023)
Currently, many people are using e-commerce. As devout Muslims adhere to Islamic law, every individual should use e-commerce applications wisely and avoid extravagance. Extravagance is spending wealth excessively on unnecessary purposes or exceeding the limits of reasonableness in shopping. Islam always teaches its followers not to be excessive (extravagant) and advocates for simplicity. The purpose of this study is to determine whether students have avoided extravagance in shopping on e-commerce platforms. The method employed in this research is descriptive research and field study. The respondents in this study consist of 30 students from Muhammadiyah University of Yogyakarta. In this research, 86% of the respondents are still exhibiting extravagant behavior, primarily due to their inability to control their finances and their preference to shop according to their desires. There are 14% of respondents who have managed to avoid extravagance, mainly because they can manage their finances well and only shop for necessities by reducing their desires, thus restraining themselves in controlling their shopping behavior